PROBLEM-BASED LEARNING DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI DI SMP AL-MUTTAQIN PATRANG JEMBER: Problem-Based Learning in Islamic Education Learning and character in Al-Muttaqin Senior High School Patrang Jember - Alek Efendi (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2019)
The learning process should be organized in an interactive and fun so that students can participate actively. Such learning can be realized by using a scientific approach. In its application can use the Learning strategy. SMP Al-Muttaqin Patrang Jember has implemented Problem Based Learning in the learning of Islamic Education and Character. This research aims to describe the Planning, Implementation, and Assessment of Problem-Based Learning Strategy in learning Islamic Education and Character in SMP Al-Muttaqin Patrang Jember School Year 2017/2018. The results of the implementation of the Problem-Based Learning (PBL) strategy in the learning of Islamic Religion and Budi Pekerti at Al-Muttaqin Junior High School Patrang Jember showed that: 1) planning was carried out at the beginning of each school year; those involved in planning activities are Headmaster, students of the curriculum and subject teachers; the development of learning devices independently; all teachers submit learning device including PAI teachers and Characteristics. 2) In The implementation of learning, the teacher presents a problem that students must observe. Then students formulate questions and collect information; then, students discuss it in groups to find solutions to problems, and the results are presented in front. 3) The teacher assesses attitude competency by observing students' behavior in or outside the classroom. Knowledge competence with written tests after the end of the learning material. Assessment of skills competencies conducted by the teacher during the learning process.